Adverse childhood events and self-harming behaviours among individuals in Ontario forensic system: the mediating role of psychopathy - Kaggwa, Mark Mohan; Chaimowitz, Gary A.; Erb, Bailea; Moulden, Heather; Prat, Sebastien; Davids, Arianna; Olagunju, Andrew T. (BMC Psychiatry, 2024)
Background: Adverse childhood events (ACEs), psychopathy, and self-harming behaviours are prevalent among individuals in the forensic psychiatry system. While existing literature suggests that ACEs, self-harm, and psychopathy are interrelated, little is known about the interplay of psychopathic traits in this relationship. The present study aimed to determine the mediating role of psychopathy in the relationship between ACEs and self-harming behaviours in forensic patients. Methods: This was a retrospective study of patients under the Ontario Review Board (ORB) between 2014 and 2015. In the analysis, we included patients with complete data on ACEs, self-harming behaviours, and a Psychopathy Checklist-Revised (PCL-R) score - a measure of psychopathic traits and their severity conducted during the reporting period. Mediation analysis was based on the Baron and Kenny approach, and sensitivity analysis was performed based on the types of ACEs. Results: The sample population (n = 593) was made up of adults, with a mean age of 41.21 (± 12.35) years and were predominantly males (92.37%). While there was a partial mediating effect of psychopathy on the relationship between ACEs and incidents of self-harming behaviours in the past year, the mediation was complete in the relationship between ACEs and a lifetime history of self-harming behaviours. Following sensitivity analysis based on the types of ACE, the mediating effects were more attributed to specific ACEs, especially having experienced child abuse or having an incarcerated household member before 18 years. Conclusion: Among forensic patients in Ontario, psychopathy mediates the relationship between experiencing ACEs and engaging in self-harming behaviours. Effective intervention to mitigate self-harming behaviours in this population should consider the potential role of psychopathy, especially among individuals who have experienced ACEs involving a history of child abuse and a family who was incarcerated.
Keywords: Adverse childhood events; Forensic; Mediating effect; Ontario Review Board; Psychopathy; Psychopathy checklist revised; PCL-R; Self-harm